AN ANALYSIS OF EDUCATION, UNEMPLOYMENT, AVERAGE CONSUMPTION PER CAPITA ON POVERTY IN NORTH SUMATERA, 2015 - Nainggolan, LoraEkana (JURNAL KEBANGSAAN, 2017)
Poverty is a problem faced by all countries in the world, especially developing countries such as Indonesia. Poverty is a measure of a countrys welfare, as measured by the powerlessness of a person to meet the minimum needs. In Indonesian poverty are unresolved issues with the reason that almost all Indonesian provinces have poverty rates over 10 percent. The object of this study is the North Sumatera Province which entitles âAn Analysis of Education, Unemployment, Average Consumption per Capita on Poverty in North Sumatera 2001-2013